Science for All: Teaching patients in a drug abuse rehabilitation center in Cabo Frio, Rio de Janeiro - Amaral Gevú, José Carlos; Santos Siqueira, Kamile; Giarrolla Ramos, Taynara; Perreira Ferreira, Gessê; Carvalho, Andressa (Guará Journal, 2017)
The purpose of this study was to evaluate the population profile and disseminate Scientific topics with teaching strategies, in order to facilitate the understanding of the subject by patients in a drug addiction rehabilitation community. The characteristics of men from "Videira Verdadeira" – a drug abuse rehabilitation center of the Comunidade dos Sinos Association, in the city of CaboFrio, RJ, were verified by filling out questionnaires; and they were given a 12 –hour- course on natural sciences. Among the 22 male subjects assessed there was a higher proportion of adults in the 30-60 years age groups (82%), with incomplete primary education(50%) and cocaine used as the main illicit substance (46%). The students’ understanding was nearly 100% of in all the subjects addressed in the classes given. We conclude that science education is extremely relevant for a population at social risk such as the patients in a drug abuse rehabilitation center, as it has become possible even for illiterate or low educated people, regardless oftheir occupation and the illegal substance used.
Keywords: Science; Education; Former drug addicted